Pengaruh Brand Image Dan Brand Awareness Terhadap Brand Loyalty Pada Produk Kosmetik Sariayu di Kota Mataram - Raniaziza, Tansya; Retnowati, Weni; Maryanti, Sri (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to determine and explain the significant influence of Brand Image and Brand Awareness on Brand Loyalty in Sariayu Cosmetic Products in Mataram City. This type of research is associative quantitative with the data collection method used, namely a survey using a questionnaire via Google Form as a research instrument with a total sample of 100 respondents and analyzed using multiple linear regression analysis via the SPSS version 25 program. The results of this research analysis show that the brand image and brand awareness variables have a positive and significant effect on brand loyalty in Sariayu cosmetic products. This shows that the better the brand image that Sariayu has, the higher the customer loyalty to the product. Apart from that, high brand awareness makes customers more likely to make repeat purchases and recommend Sariayu products to others. The results of instrument tests and classical assumption tests show that the data in this study is proven to be valid and all data is normally distributed. These findings have the implication that to increase brand loyalty, companies need to carry out effective marketing strategies to strengthen brand image and increase brand awareness of their products. It is hoped that this research can become a reference for PT. Martina Berto Tbk as a Sariayu producer in increasing competitiveness and maintaining customer loyalty amidst increasingly tight competition in the cosmetics industry.